Los derechos de propiedad intelectual al servicio de las TIC: ¿harina de otro costal? - Acea Valdés, Yeney (2023)
Intellectual property rights that constitute assets of great value for companies, hence the frequent interest in their adequate protection, especially in the context of ICT, where the impact is much greater. The objective of this work is to analyze the intellectual property rights that have the greatest incidence in the world of ICT, as well as their forms of commercialization; through documentary content analysis and the use of theoretical and analytical methods. As a conclusion, the criterion of proximity between the concepts of intellectual property rights and ICT is reinforced, as well as the elements that should not be ignored at the time of commercial-ization.